The Efficiency of Reactive Power Compensation of High Power Nonlinear Loads - Wosik, J.; Kalus, M.; Kozlowski, A.; Miedzinski, B.; Habrych, M. (Elektronika ir Elektrotechnika, 2013)
The paper presents and discusses the problems associated with reactive power compensation of nonlinear loads. Analytical results and simulation studies for selected high power drive used in mine when apply dynamic compensation together with active harmonics filters are presented. It was found that application of active power filters allows for compensation high current harmonics in general, and suppression of as reactive power flows as well as current harmonics in the network. On the basis of results conclusions on efficiency of the active on-line compensation of non-linear loads of a high power are formulated. DOI: http://dx.doi.org/10.5755/j01.eee.19.7.5158